Perception of Housing Quality by Households in Peri-Urban Neighbourhoods of Owerri Municipality (CSID Journal of Infrastructure Development, 2022)
Basic housing infrastructure influences the comfort of several residents. There are, however, indications that the residents in severalurban housing estates in Nigeria are dissatisfied with their housing infrastructures and maintenance. Therefore, this study focuses on evaluating the relationship between the quality of housing infrastructure and the decision of occupants on where to live. Thisstudy involved the application of a quantitative approach with the aid of a structured questionnaire to collect data from residents. The survey was conducted in six selected neighbourhoods of Owerri Municipal area with the occupants as respondents (n=399). Moreover, the chi-square test of independence was applied to determine the relationshipbetween the quality of housing infrastructure and the decision to live in either the urban areas or move to the peripheries. The result (χ2(39) = 920.41, p < .001) showed a significant association and this implies potential occupants should be consulted more in the conceptualisation and execution of housing projects to ensure their expectations are met.